Pengaruh Kemandirian Dan Gaya Belajar TerhadapPrestasi Belajar Siswa Kelas Tinggi SD Muhammadiyah 11Mangkuyudan Surakarta Tahun 2015/ 2016 - Esti, Ervina, Minsih, S.Ag., M.Pd (2016)
This research aims to know determine the influence of independence towards learning achievements, determinethe influence of learning style towards learning achievements, and determine influence independence among and learning style against the learning achievements. Populations in this research are 111 high-grade primary school students of Muhammadiyah 11 Mangkuyudan Surakarta and samples were taken as 53 students. Data collection technique used questionnaire and documentation. Data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination, SR and SE. Based on the results of multiple linear regression equation Y = 58,644 + 0,131 + 0,162 . The results of research shown: (1) There are some independence effect on the student learning, by , (2.233 > 2.008) and the significance value <0.05, its 0.030. (2) There are some learning style effect on the student learning achievement, by , (2,958 > 2.008) and the significance value <0.05 its 0.005. (3) There are some effect independence and learning style to learning achievement. It is based on test F known that (15.151 > 3.20) and a significance value <0.05 is 0.000. The coefficient determination calculation known that both of independence and learning style are giving effect to student learning achievement by together with contribution up to 37,7%.